Electrical, thermal, and H2O and CO2 poisoning behaviors of PrNi0.5Co0.5O3-δ electrode for intermediate temperature protonic ceramic electrochemical cells. (16th June 2022) - Sozal, Md Shariful Islam; Tang, Wei; Das, Suprabha; Li, Wenhao; Durygin, Andriy; Drozd, Vadym; Zhang, Cheng; Jafarizadeh, Borzooye; Wang, Chunlei; Agarwal, Arvind; Ding, Dong; Cheng, Zhe
Abstract: PrNi0.5 Co0.5 O3-δ (PNC) exhibits adequate total electrical conductivity (∼300 S/cm at 400–600 °C) and moisture has no significant effect on it. The thermal expansion coefficient of PNC is 17.6 × 10 −6 /K by dilatometry and 18.43 × 10 −6 /K by in situ XRD. PNC also demonstrates chemical stability against H2 O and CO2 . However, PNC symmetrical cell over proton-conducting BaZr0.4 Ce0.4 Y0.1 Yb0.1 O3-δ (BZCYYb4411) electrolyte shows significant H2 O and CO2 poisoning when those are introduced into O2 –N2 mixture. In comparison, symmetrical cells with PNC electrode over the oxygen ion conducting Ce0.9 Gd0.1 O2-δ (GDC) electrolyte show no H2 O and CO2 poisoning under similar conditions. It is hypothesized that poisoning from H2 O and CO2 of the PNC proton conducting symmetrical cell is caused by their adsorption on the BZCYYb4411 electrolyte instead of PNC electrode. Such a hypothesis is supported by the H2 O and CO2 adsorption behaviors on PNC and BZCYYb4411 powder surfaces, as measured by temperature programmed desorption (TPD). Highlights: PrNi0.5 Co0.5 O3-δ exhibits adequate total electrical conductivity. PrNi0.5 Co0.5 O3-δ has high thermal expansion coefficient. PrNi0.5 Co0.5 O3-δ is chemically stable against H2 O and CO2 . Significant H2 O and CO2 poisoning for PrNi0.5 Co0.5 O3-δ proton-conducting symmetrical cell. Poisoning is due to H2 O and CO2 adsorption on BaZr0.4 Ce0.4 Y0.1 Yb0.1 O3-δ electrolyte.